Progress and prospects of recycling technology for carbon fiber reinforced polymer - Yuan, Min; Li, Zihao; Teng, Zhan (Frontiers in Materials, 2024)
This paper provides a comprehensive review of current and prospective technologies for recycling carbon fiber reinforced polymer (CFRP), addressing the growing need for sustainable disposal and resource recovery driven by increasing CFRP applications. Four primary recycling methods are discussed: incineration, physical recycling, chemical recycling, and thermal recycling. Incineration, while offering energy recovery, is unsustainable due to limited material recovery and environmental pollution. Physical recycling, utilizing mechanical processes, is cost-effective but results in significant fiber degradation, restricting applications to low-value fillers. Chemical recycling, involving solvent or acid-based resin decomposition, can yield high-quality fibers but faces challenges regarding environmental impact, process efficiency, and economic viability. Thermal recycling, encompassing pyrolysis in various configurations (conventional, fluidized bed, and microwave), emerges as the most promising approach, offering reasonable recovery rates and acceptable fiber properties, albeit with concerns about energy consumption and potential fiber damage. The review critically evaluates each method based on recovery efficiency, recovered fiber quality, environmental impact, and economic feasibility. It highlights the need for future research focusing on developing greener chemical solvents and catalysts, optimizing thermal processes and exploring product valorization, and investigating novel recycling technologies such as supercritical fluids, bio-based methods, and electrochemical approaches. Furthermore, it emphasizes the importance of establishing comprehensive performance evaluation standards for recycled fibers, exploring surface modification techniques, and expanding application possibilities. Life cycle assessment, economic analysis, and strengthened collaborations among academia, industry, and government are also crucial for advancing CFRP recycling towards industrialization and promoting a circular economy within the composites sector.